2013
DOI: 10.1088/0004-637x/770/1/63
|View full text |Cite
|
Sign up to set email alerts
|

The Imacs Cluster Building Survey. Iii. The Star Formation Histories of Field Galaxies

Abstract: Using data from the IMACS Cluster Building Survey and from nearby galaxy surveys, we examine the evolution of the rate of star formation in field galaxies from z = 0.60 to the present. Fitting the luminosity function to a standard Schechter form, we find a rapid evolution of M * B consistent with that found in other deep surveys; at the present epoch M * B is evolving at the rate of 0.38Gyr −1 , several times faster than the predictions of simple models for the evolution of old, coeval galaxies. The evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Some of these observations were drawn from the IMACS Cluster Building Survey (ICBS, Dressler et al 2013;Oemler et al 2013aOemler et al , 2013b. In a combined fit over the global constraints and the stellar masses and SFRs of each galaxy, they found the best-fit T 0 and τ for the 2094 galaxies (see their Figure 9).…”
Section: The Gladders Et Al Galaxy Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these observations were drawn from the IMACS Cluster Building Survey (ICBS, Dressler et al 2013;Oemler et al 2013aOemler et al , 2013b. In a combined fit over the global constraints and the stellar masses and SFRs of each galaxy, they found the best-fit T 0 and τ for the 2094 galaxies (see their Figure 9).…”
Section: The Gladders Et Al Galaxy Samplementioning
confidence: 99%
“…Inspired by the fact that the global SFRD is well fit by a lognormal in time, Gladders et al (2013, hereafter G13) suggested that this form might also describe the SFHs of individual galaxies (G13; Dressler et al 2013Dressler et al , 2017Oemler et al 2013a;Abramson et al 2015Abramson et al , 2016. The log-normal SFR is given by the expression where A, T 0 , and τ are free parameters (throughout the paper, t refers to the time since the big bang, not lookback time).…”
Section: Introductionmentioning
confidence: 99%
“…Using the large sample of spectroscopic redshift of MACS1206 , which is biased against red galaxies, we found that less than 3% of the stellar mass is in bluer galaxies. We estimate galaxy stellar masses from the z band luminosity and V − z color using the relation between M/L and galaxy color derived using the Bruzual & Charlot (2003) stellar population synthesis models (like that of Bell & de Jong 2001; and similarly to Kravtsov et al 2014;Boselli et al 2014;Fritz et al 2014;Budzynski et al 2014;Gladders et al 2013;Oemler et al 2013;, to only mention cluster 2 http://www.naoj.org/Observing/Instruments/SCam/ works that have appeared in the last year). This single-color estimate of stellar mass is found to give values consistent with full-SED fitting up to z ∼ 2 (Koyama et al 2013).…”
Section: Samples and Datamentioning
confidence: 99%
“…Such issues and the results of our own analyses have led us to an alternative paradigm. Over the course of a number of papers- Dressler et al (2013); Oemler et al (2013); Gladders et al (2013); Abramson et al (2013Abramson et al ( , 2014Abramson et al ( , 2015-we have developed a framework in which galaxy star formation histories [SFHs, records of in situ stellar mass (M * ) production] are not maintained or squelched, but extended or compressed, rising and falling smoothly over time. The cessation of star formation is thus an extension of the slowing of star formation, and so the natural conclusion of the galaxy lifecycle, not the untimely termination of an otherwise healthy existence.…”
Section: Introductionmentioning
confidence: 99%